Komponen Kelayakan Isi dan Bahasa Modul Pembelajaran Fisika Berbasis Multirepresentasi SMK Kelas X Semester Genap - Wachidah Putri Ramadhani; I Ketut Mahardika; Yushardi Yushardi (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2016)
The article of content feasibility and language feasibility component for physics SMK grade X even semester based on multirepresentation is aimed to describe feasibility of content and feasibility of language that module. The plan of research development used steps that suitable with design modification model 4D which spreading step wasn’t done. Feasibility of content of this modul can be seen from logic validator result that was feedback from three postgraduate lecturers of science education consentrate to physics for the content of physics based on multirepresentation, empiric validation by increasing student multirepresentation ability result. Language feasibility modul can be seen from logic validasi result that is feedback from three postgraduade lecturers of science education consentrate to physics for the language. That is used in that physics module based on multirepresentation, and empiric validation by student readable test. Based on the data got, content feasibility covers alignment with SK and KD, lesson, alignment with student development and society need, knowledge substance, and life skill, insight to advance and work out, and deverse of social value, it is seen from logic validation that has enough category. Being seen from empiric validation by student multirepresentation result ability encreasing development test, include in high category. Language feasibility that is readable, suitability with Indonesian rule, speaking logic, by seeing from logic validation that has valid category. Beeing seen from empiric validation by development test by using readable test that has high category.